2017
DOI: 10.1155/2017/6358680
|View full text |Cite
|
Sign up to set email alerts
|

Geofluids Assessment of the Ayub and Shafa Hot Springs in Kopet-Dagh Zone (NE Iran): An Isotopic Geochemistry Approach

Abstract: Geothermal energy has a wide range of uses in our life. It is very important to characterize the temperature and the depth of geothermal reservoirs. The aim of this paper is the determination of type, origin source of water temperature, and depth of water circulation in the Ayub-Peighambar and Shafa (AP and SH) hot springs, located in NE Iran, using hydrogeochemistry and environmental isotopes (2H and18O). AP hot spring has elevated temperature (36–40°C) and as such is very important for balneotherapy and geot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…To validate the developed Iran MWLs, they were compared with fresh karstic springs across Iran. The δ 18 O, δ 2 H, electrical conductivity (EC), and d-excess values for over 200 karstic freshwater springs are shown in Supplementary Table S3 [17,19,20,43,45,54,[61][62][63][64][65][66][67][68][69][70][71]. Evaporation did not markedly affect the selected karstic springs, and the EC of the karstic springs water was < 1000 μS/cm.…”
Section: Developing Mwls For Iranmentioning
confidence: 99%
“…To validate the developed Iran MWLs, they were compared with fresh karstic springs across Iran. The δ 18 O, δ 2 H, electrical conductivity (EC), and d-excess values for over 200 karstic freshwater springs are shown in Supplementary Table S3 [17,19,20,43,45,54,[61][62][63][64][65][66][67][68][69][70][71]. Evaporation did not markedly affect the selected karstic springs, and the EC of the karstic springs water was < 1000 μS/cm.…”
Section: Developing Mwls For Iranmentioning
confidence: 99%
“…The increasing of temperature will decrease the magnetic property of the rock, so that the rock will tend to be lower magnetic field if it is compared to the surrounding rock (Telford et al, 1990). Mohammadzadeh & Kazemi (2017) also found that lower magnetic value at the surrounding area of the hot spring in Iran. Hence, the presence of hot spring is very possible produced by pathway of rock fracture.…”
Section: Results and Discussion The Magnetic Resultsmentioning
confidence: 84%
“…The CO6, CO8, and SJ11 sources are peripheral and shallow waters; however, the HCO 3 content is not relatively high. The sources present on steam-heated waters (CO4 and CO12) are characterized by moderate contents of [30].…”
Section: Resultsmentioning
confidence: 99%
“…According to the ternary diagrams, the Coconuco and San Juan sectors present considerable concentrations of SO 4 , Na, Ca, and HCO 3 which indicates the possibility of meteoric water circulating through the faults of the region and the exothermic reactions in the interior generate an increase in the temperature of the fluids [30]. On the other hand, the sources presented a classification of immaturity and the equilibrium clearly shifts towards Mg, which means that the sources acquire Mg with the decrease in temperature [34].…”
Section: Geofluidsmentioning
confidence: 99%